Effective elimination of Staphylococcal contamination from hospital surfaces by a bacteriophage–probiotic sanitation strategy: a monocentric study - Maria D'Accolti (Microbial Biotechnology, 2019)
Summary Persistent contamination of hospital surfaces and antimicrobial resistance (AMR) is recognized as major causes of healthcare‐associated infections (HAI). We recently showed that probiotic‐based sanitation (PCHS) can stably decrease surface pathogens and reduce AMR and HAIs. However, PCHS action is slow and non‐specific. By contrast, bacteriophages have been proposed as a decontamination method as they can rapidly attack specific targets, but their routine application has never been tested. Here, we analysed the feasibility and effectiveness of phage addition to PCHS sanitation, aiming to obtain a rapid and stable abatement of specific pathogens in the hospital environment. Staphylococcal contamination in the bathrooms of General Medicine wards was analysed, being those areas the most contaminated and Staphylococci the most prevalent bacteria in such settings. Results showed that a daily phage application by nebulization induced a rapid and significant decrease in Staphylococcus spp. load on treated surfaces, up to 97% more than PCHS alone (P < 0.001), suggesting that such a system might be considered as a part of prevention and control strategies, to counteract outbreaks of specific pathogens and prevent associated infections.